Superior Capsular Reconstruction - a comprehensive review of the current literature - Maria Clara Pacheco Correia (2020)
Rotator cuff tears are one of the most common shoulder pathologies, and up to 40% are considered massive rotator cuff tears. Chronic tears can me deemed irreparable due to several factors, and there is still no good treatment option. Numerous alternatives have been considered, but none has been able to restore functional movement of the arm whilst maintaining stability of the joint at a low complication and failure rate. Over the past years, a new technique, Superior Capsular Reconstruction, has gained a central role in the conversation over treatment of massive irreparable rotator cuff tears. By performing a systematic search on Medline database with the queries "superior capsular reconstruction" and "superior capsule reconstruction", and including all sixty-two original articles on the subject, this review of the literature aimed at gathering all available evidence on Superior Capsular Reconstruction, while preforming a critical interpretation and summarization of the perks and pitfalls of this surgical technique. In fact, in a field where no good solutions have yet arisen, Superior Capsular Reconstruction emerges as a better and viable treatment option. However, this technique is still very complex and difficult to reproduce, and there are yet many doubts needing clarification, namely regarding surgical indications, technical methodology and variations, and mid and long term efficacy.